1980
DOI: 10.1051/rphysap:01980001505094500
|View full text |Cite
|
Sign up to set email alerts
|

High injection effects on conductivity and carrier lifetime in P-type silicon material

Abstract: High injection changes in carrier lifetime, mobility and density of a semiconductor material are analyzed using the changes in carrier recombination or diffusion processes and in equilibrium of the donor-acceptor centers (including defect centers). The analysis especially involves the variations with carrier injection Δ of state charge q0 and energy level E occupancy state nE(pE) of the material recombination or donor (acceptor) centers, taking into account the Δ, band-gap energy level E, material Fermi-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The diffusion length reaches a maximum value at the injection level within an order of magnitude of the base doping. It was shown that the minority carrier lifetime and diffusion length could be increased at high injection level, because of enhanced density of ionized centers [12], [24]. It should be mentioned that the diffusion length range for extreme boundary conditions (n=0, 1/2) significantly increases for high-level injection conditions.…”
Section: Diffusion Length Measurementsmentioning
confidence: 99%
“…The diffusion length reaches a maximum value at the injection level within an order of magnitude of the base doping. It was shown that the minority carrier lifetime and diffusion length could be increased at high injection level, because of enhanced density of ionized centers [12], [24]. It should be mentioned that the diffusion length range for extreme boundary conditions (n=0, 1/2) significantly increases for high-level injection conditions.…”
Section: Diffusion Length Measurementsmentioning
confidence: 99%
“…-The general forms of the photoresponses i(t) and 0394V03C3(t) are the same at 1.06 03BCm and 0.53 gm. These two types of photoresponses, which correspond respectively to free electrons or holes (photocurrent in,p(t)) and to the variation in the conductivity induced in the material, may be related to diverse phenomena (see [4]). They are compared in figure 7.…”
Section: K And#x3e; T And#x3ementioning
confidence: 99%
“…The values of 03C403C31 and 'ta2 are given in figure 7 ; note that they are large. This is therefore not the response of a homogeneous material such as bulk silicon, in which the lifetime of free carriers may be measured from the photoconductivity decay, at least in the low to mean carrier injection range [4,13,14].…”
Section: K And#x3e; T And#x3ementioning
confidence: 99%
See 2 more Smart Citations